Design of a distributed hybrid electric propulsion system for a light aircraft based on genetic algorithm - Economou, John T.; Tsourdos, Antonios; Wang, Siqi (AIAA, 2019)
Hybrid aircraft is a new attempt for next-generation aircraft, they are environmentally friendly and highly efficient. This paper proposes a new type of hybrid electric propulsion system for light aircraft, which integrated distributed propulsion concept and more electric aircraft concept together to improve aircraft performance. Based on the mission requirements and unique system configuration, all components, including engine, generator and motors are intelligently selected. The sizing problem can be divided into two parts. The power source part applied a non-dominated sorting genetic algorithm to choose components and simultaneously minimized total weight and fuel consumption. The rest of the system used a conventional genetic algorithm, which minimized weight and guaranteed that all selected motors can output enough power. In the end, by applying a simple deterministic energy management strategy, the new system achieved a 12% fuel consumption reduction.